Adoptive cellular immunotherapy for virus‐associated cancers: a new paradigm in personalized medicine. Issue 4 (10th January 2017) - Smith, Corey; Khanna, Rajiv
Abstract : Persistent viral infections are associated with the majority of human cancers where infectious agents have been recognized as the primary etiological agent. These viruses contribute to the malignant transformation of human cells either through the expression of oncogenic proteins or chronic inflammation. In spite of the high prevalence of these viral infections in humans, only a small proportion of these individuals who may have an underlying immune defect develop malignant disease. Furthermore, many of these viruses have evolved unique mechanisms to avoid the host immune system to successfully establish latent infection with limited gene expression. Technological advances in delineating the role of cellular immune responses in the control of viral infections and ability to rapidly expand these effector cells in vitro have provided an important platform for the development of novel immunotherapeutic strategies to treat virus‐associated cancers. While autologous T cell therapies have provided promising results, development of 'off‐the‐shelf' third‐party allogeneic virus‐specific T cell therapies have emerged as powerful tools to treat many of the virus‐associated diseases. It is anticipated that adoptive T cell therapy in combination with newly emerging immune checkpoint inhibitors and therapeutic vaccines will provide opportunities to successfully treat advanced metastatic virus‐associated cancers which are currently not amenable to standard therapeutic strategies. Abstract : The April 2017 issue of Immunology & Cell Biology contains a Special Feature on Cancer Immunotherapy. This series of reviews highlights some of the recent advances in mobilizing effective host immunity to cancer. Cancer immunotherapy is at a critical and exciting stage of development. Progress in our understanding of cancer immunotherapy has been dramatic over recent years and we have selected six articles to highlight in this Special Feature. The Special Feature begins with an overview of the approaches to targeting inflammation in the cancer microenvironment and follows with a focus of extracellular adenosine as a major immunosuppressive metabolite in tumours. Two subsequent articles detail advances in antibody engineering for engaging the ideal effector responses in tumours and the Special Feature finishes with two articles that explore new approaches in adoptive cellular therapy targeted at tumor and virus specific antigens in tumors. Immunology & C ell Biology thanks the coordinator of this Special Feature ‐ Mark Smyth ‐ for his planning and input.